2015
DOI: 10.1016/j.powtec.2014.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of influence of process variables on mechanical strength, size and homogeneity of pharmaceutical granules produced by fluidised hot melt granulation

Abstract: Publisher rights This is the author's version of a work that was accepted for publication in Powder Technology. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Powder Technology, vol 272, issue March 2015 doi: 10.1016/j.powtec.2014.11.042. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
(59 reference statements)
1
15
0
Order By: Relevance
“…On the other hand, the loss of crystal water from α-lactose monohydrate did not appear in the same thermal range as in the raw material (Table 3), attributed to the free volume experienced when in contact with the polymer, lowering the crystal vaporization temperature. Also, the normalized integration of the signal intensity demonstrates a decrease when using a higher binder content [8].…”
Section: Differential Scanning Calorimetrymentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, the loss of crystal water from α-lactose monohydrate did not appear in the same thermal range as in the raw material (Table 3), attributed to the free volume experienced when in contact with the polymer, lowering the crystal vaporization temperature. Also, the normalized integration of the signal intensity demonstrates a decrease when using a higher binder content [8].…”
Section: Differential Scanning Calorimetrymentioning
confidence: 94%
“…Following particle agglomeration and consolidation, the granules are cooled to room temperature and a solid end product with a granular structure is formed [7][8][9][10]. For this granulation method, the drying step, which is required after wet granulation, is eliminated, hence the process time and energy requirements are significantly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Size enlargement is initiated by the addition of liquid binder which wets the powder material and acts as a bonding agent. Wet granulation manufacturing processes can be complex and controlled by multi-factorial relationships between materials and process parameters [1][2][3][4][5][6]. It has been reported that the granule properties were affected by the relative composition of initial feed materials [3].…”
Section: Introductionmentioning
confidence: 99%
“…Tablets are the most preferred dosage form with respect to patient acceptability, flexibility in dose adjustment, easy manufacturing, and better stability [1,2]. Irrespective of the nature of the drug and its manufacturing technique, tablets should meet some strict requirements in terms of mechanical strength, disintegration, and drug release [3][4][5]. A variety of techniques are available for tablet preparation among which direct compression is mostly preferred due to simplicity, cost-effectiveness, and less number of involved steps [6,7].…”
Section: Introductionmentioning
confidence: 99%